The effects of opium uses on syntax score of angiography patients with coronary artery disease (CAD). (2nd October 2022) - Moezi, Seyyed Ali; Azdaki, Nahid; Kazemi, Toba; Partovi, Neda; Hanafi Bojd, Nazanin; Mashreghi Moghaddam, Hamid Reza; Hamidi, Fatemeh; Khosravi Bizhaem, Saeede; Soltani, Maryam; Niroomand, Mohammad Saleh; Khazdair, Mohammad Reza
Abstract: Opium has been used traditionally for lowering blood lipids, diabetes, cancer, and postpone of cardiac diseases. The coronary angiography patients were divided to opium user and control group. SYNTAX score, serum lipid profile, left ventricular ejection fraction (LVEF), systolic and diastolic blood pressure (SBP and DBP) were measured in the case and control groups. The SBP, LVEF, serum levels of triglycerides, creatinine and SYNTAX score in opium user group was significantly lower than non-user group ( p  < 0.05 to p  < 0.01). Although, opium consumption reduced some risk factors, LVEF a key variable for the diagnosis and management of heart failure was also reduced.